Students' Learning Styles (VRAK Model) in Learning English - Noviska, Della Wilza; Anastasia, Faurina (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2023)
Many teachers still remain unaware of their students' learning styles, which hinders their ability to consider individual student preferences and optimize instructional methods. This research aims to investigate students' learning styles using VRAK (visual, read-write, audio, and kinesthetic) model by Fleming in English language learning. The study adopted a qualitative research design and utilized the case study method involving 27 students at Senior High School 1 Sungai Penuh, Jambi. Data were collected through interviews and observations. Qualitative thematic analysis was employed, involving three stages: data reduction, data display, and conclusion drawing or verification. The findings reveal that 56% of the students possess a kinesthetic learning style. The remaining 22%, 11%, and 11% of students have visual, auditory, and read-write learning styles, respectively. Understanding students' diverse learning styles in the context of English language learning has significant implications for instructional practices. It enables teachers to optimize their efforts in selecting and implementing differentiated teaching methods tailored to their students' individual needs.Keywords: English learning, Learning styles, VRAK